Management strategies during climate and menopause. Practical guide to quick attention - Ayala-Peralta, Félix Dasio (2020)
The climacteric is a stage of a woman's physiological life where climacteric symptoms and the appearance of chronic diseases typical of this period appear, which affect the quality of life related to female health. The clinic during the climacteric is variable; but, vasomotor symptoms and genitourinary menopause syndrome are cardinal symptoms of menopause. The strategies in the management of the climacteric have changed in the last years due to the results of recent investigations in this area, since not only are hormonal and non-hormonal therapy used; Instead, lifestyle modifications, including diet and exercise, can help reduce menopausal symptoms.